Distinct cytokine profiles associated with COVID-19 severity and mortality - Dorgham, Karim; Quentric, Paul; Gökkaya, Mehmet; Marot, Stéphane; Parizot, Christophe; Sauce, Delphine; Guihot, Amélie; Luyt, Charles-Edouard; Schmidt, Matthieu; Mayaux, Julien; Beurton, Alexandra; Le Guennec, Loic; et al. (The Journal of allergy and clinical immunology, 2021)
BACKGROUND: Markedly elevated levels of proinflammatory cytokines and defective type-I interferon responses were reported in patients with coronavirus disease 2019 (COVID-19). OBJECTIVE: We sought to determine whether particular cytokine profiles are associated with COVID-19 severity and mortality. METHODS: Cytokine concentrations and severe acute respiratory syndrome coronavirus 2 antigen were measured at hospital admission in serum of symptomatic patients with COVID-19 (N = 115), classified at hospitalization into 3 respiratory severity groups: no need for mechanical ventilatory support (No-MVS), intermediate severity requiring mechanical ventilatory support (MVS), and critical severity requiring extracorporeal membrane oxygenation (ECMO). Principal-component analysis was used to characterize cytokine profiles associated with severity and mortality. The results were thereafter confirmed in an independent validation cohort (N = 86). RESULTS: At time of hospitalization, ECMO patients presented a dominant proinflammatory response with elevated levels of TNF-α, IL-6, IL-8, and IL-10. In contrast, an elevated type-I interferon response involving IFN-α and IFN-β was characteristic of No-MVS patients, whereas MVS patients exhibited both profiles. Mortality at 1 month was associated with higher levels of proinflammatory cytokines in ECMO patients, higher levels of type-I interferons in No-MVS patients, and their combination in MVS patients, resulting in a combined mortality prediction accuracy of 88.5% (risk ratio, 24.3; P < .0001). Severe acute respiratory syndrome coronavirus 2 antigen levels correlated with type-I interferon levels and were associated with mortality, but not with proinflammatory response or severity. CONCLUSIONS: Distinct cytokine profiles are observed in association with COVID-19 severity and are differentially predictive of mortality according to oxygen support modalities. These results warrant personalized treatment of COVID-19 patients based on cytokine profiling.
Keywords: senioři; umělé dýchání; stupeň závažnosti nemoci; serum cytokines; SARS-CoV-2; cytokiny; Middle Aged; mužské pohlaví; COVID-19; Adult; Cytokines; ženské pohlaví; Humans; principal-component analysis; type-I interferons; lidé středního věku; respiratory severity; dospělí; Female; Aged; Severity of Illness Index; mortality; lidé; Male; Respiration, Artificial